Your health is in your mouth: A comprehensive view to promote general wellness - Barranca-Enríquez, Antonia; Romo-González, Tania (Frontiers in Oral Health, 2022)
Abstract Objectives: Even though various studies recognize the importance of the oral cavity for general health, in multidisciplinary professional practice it is almost always excluded and on an individual basis, very commonly neglected. Oral diseases are preventable, still, they are highly prevalent. Although some studies consider oral health within integral health, at present there is no model in which the mouth is integrated within other levels for the achievement of well-being. The objective of this article was to carry out a narrative review of the importance of oral health and its connection with well-being and, based on these findings, propose a complex and comprehensive perspective for approach and care. Methods: The databases MEDLINE, PubMed, and Google Scholar were revised for randomized controlled trials and systematic reviews that included search terms related to oral health and its relationship with the general health in its different levels (physical, psychological, social and environmental). Results: The main contribution of this narrative review is to highlight the importance of the oral cavity to well-being and human development, and its relationship with general health. Particularly, this paper proposed an integrative model in which the mouth is the first step for well-being and an integrative and multidisciplinary approach for promotion of oral care and general health. Conclusions: The effort on the part of oral health professionals is essential for the people’s well-being and must be integrated as part of health promotion. Dental treatments alone cannot solve this problem, it requires a comprehensive, and radically different approach to face this global oral health challenge.